HIV Infection of Macrophages: Implications for Pathogenesis and Cure - Kiera Leigh Clayton; Victor Garcia; Janice E. Clements; Bruce D. Walker (Case Western Reserve University, 2017)
Although CD4+ T cells represent the major reservoir of persistent HIV and SIV infection, accumulating evidence suggests that macrophages also contribute. However, investigations of the role of macrophages are often underrepresented at HIV pathogenesis and cure meetings. This was the impetus for a scientific workshop dedicated to this area of study, held in Cambridge, MA in January 2017. The workshop brought together experts in the fields of HIV/SIV immunology/virology, macrophage biology and immunology, and animal models of HIV/SIV infection to facilitate discussions regarding the role of macrophages as a physiologically relevant viral reservoir, and the implications of macrophage infection for HIV pathogenesis and cure strategies. An emerging consensus that infected macrophages likely persist in the setting of combination antiretroviral therapy, driving persistent inflammation and contributing to the viral reservoir, indicate the importance of addressing macrophages as well as CD4+ T cells with future therapeutic strategies.